Weaponising migration status in domestic and family violence: the violence of everyday bordering - Segrave, Marie Therese (The borders of violence, 2024)
This chapter details how temporary migration status is weaponised by perpetrators in the context of domestic and family violence (DFV). We argue that the border is omnipresent in the intimate and familial violence that is enacted against temporary visa holders and as such, we can understand aspects of DFV and the response as part of everyday bordering. In recognising the role of the border and the influence of the migration system in differentiating victims of DFV based on their migration status, this chapter argues that the state plays an active role in sustaining DFV, which we frame as a form of structural violence.